2009
DOI: 10.1037/a0015166
|View full text |Cite
|
Sign up to set email alerts
|

The role of mindfulness in predicting individual performance.

Abstract: Mindfulness refers to an individual difference variable regarding the degree to which a person is in the present moment (K. W. Brown & R. M. Ryan, 2003). Despite a growing interest in the benefits of mindfulness in health and clinical outcomes, little research has explored whether mindfulness relates to individual performance. The authors examined whether mindfulness was related to performance among a group of MBA students (N ϭ 149). The results show that mindfulness interacted with gender to predict performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 51 publications
(59 reference statements)
1
38
0
1
Order By: Relevance
“…Furthermore, a mindfulness approach might be of help by training students to focus on the present moment and to envision situations objectively, which should help them see future events and challenges, like academic exams in a more neutral/positive light rather than as potential disasters and catastrophes. The results of a study on the positive associations between mindfulness and performance among young adults support this approach (Shao & Skarlicki, 2009). Another important ingredient for preventing chronic stress could be to increase their awareness of the importance of sleep and recovery (Söderström et al, 2004).…”
Section: Discussionmentioning
confidence: 75%
“…Furthermore, a mindfulness approach might be of help by training students to focus on the present moment and to envision situations objectively, which should help them see future events and challenges, like academic exams in a more neutral/positive light rather than as potential disasters and catastrophes. The results of a study on the positive associations between mindfulness and performance among young adults support this approach (Shao & Skarlicki, 2009). Another important ingredient for preventing chronic stress could be to increase their awareness of the importance of sleep and recovery (Söderström et al, 2004).…”
Section: Discussionmentioning
confidence: 75%
“…In addition to mindfulness being related to lower turnover intentions, research suggests that more mindful employees also show greater task performance (Dane & Brummel, 2014;Reb et al, 2015;Shao & Skarlicki, 2009). Beal, Weiss, Barros, and MacDermid (2005) argue that affective processes, such as rumination, arousal, or emotional exhaustion take attentional resources away from the task at hand, thus negatively influencing performance.…”
Section: Introductionmentioning
confidence: 99%
“…Other correlational studies compared individual mindfulness baseline with academic performance and found a direct correlation between mindfulness attention and academic success (Martín, Leon & Vicente, 2007). The relationship between mindfulness and task performance is currently being tested in a large number of studies and results tend to confirm the hypothesis that mindfulness training enhances performance, particularly in sports (Cranson et al, 1991;Sugiura, 2003;Oyan, 2006;Moore & Malinowski, 2009;Shao & Skarlicki, 2009). …”
Section: Academic and Sport Performancementioning
confidence: 90%
“…Significant enhancement in academic performance has been appreciated in experimental groups submitted to training in meditation with respect to control groups showing no significant improvement (Beauchemin, Hutchins & Patterson, 2006;Shao & Skarlicki 2009). Other correlational studies compared individual mindfulness baseline with academic performance and found a direct correlation between mindfulness attention and academic success (Martín, Leon & Vicente, 2007).…”
Section: Academic and Sport Performancementioning
confidence: 99%